Multi-institutional intervention to improve patient perception of physician empathy in emergency care. Issue 6 (21st December 2021) - Pettit, Katie; Messman, Anne; Scott, Nathaniel; Puskarich, Michael; Wang, Hao; Alanis, Naomi; Dehon, Erin; Konrath, Sara; Welch, Robert D; Kline, Jeffrey
Abstract : Background: Physician empathy has been linked to increased patient satisfaction, improved patient outcomes and reduced provider burnout. Our objective was to test the effectiveness of an educational intervention to improve physician empathy and trust in the ED setting. Methods: Physician participants from six emergency medicine residencies in the US were studied from 2018 to 2019 using a pre–post, quasi-experimental non-equivalent control group design with randomisation at the site level. Intervention participants at three hospitals received an educational intervention, guided by acognitivemap (the 'empathy circle'). This intervention was further emphasised by the use of motivational texts delivered to participants throughout the course of the study. The primary outcome was change in E patient perception of resident empathy (Jefferson scale of patient perception of physician empathy (JSPPPE) and Trust in Physicians Scale (Tips)) before (T1) and 3–6 months later (T2). Results: Data were collected for 221 residents (postgraduate year 1–4.) In controls, the mean (SD) JSPPPE scores at T1 and T2 were 29 (3.8) and 29 (4.0), respectively (mean difference 0.8, 95% CI: −0.7 to 2.4, p=0.20, paired t-test). In the intervention group, the JSPPPE scores at T1 and T2 were 28 (4.4) and 30 (4.0), respectively (mean difference 1.4, 95% CI: 0.0 to 2.8, p=0.08). In controls, the TIPS at T1 was 65 (6.3) and T2 was 66 (5.8) (mean difference −0.1, 95% CI: −3.8 to 3.6, p=0.35). In the intervention group, the TIPS at T1 was 63 (6.9) and T2 was 66 (6.3) (mean difference 2.4, 95% CI: 0.2 to 4.5, p=0.007). Hierarchical regression revealed no effect of time×group interaction for JSPPPE (p=0.71) nor TIPS (p=0.16). Conclusion: An educational intervention with the addition of text reminders designed to increase empathic behaviour was not associated with a change in patient-perceived empathy, but was associated with a modest improvement in trust in physicians.